Differential involvement of ipsilateral and contralateral spinal cord astrocyte D‐serine in carrageenan‐induced mirror‐image pain: role of σ1 receptors and astrocyte gap junctions - Choi, Hoon‐Seong (Br J Pharmacol, 2018)
BACKGROUND AND PURPOSE: Although we have recently demonstrated that spinal astrocyte gap junctions mediate the development of mirror‐image pain (MIP), it is still unclear which astrocyte‐derived factor is responsible for the development of MIP and how its production is controlled. In the present study, we focused on the role of ipsilateral versus contralateral D‐serine in the development of MIP and investigated the possible involvement of σ1 receptors and gap junctions in astrocyte D‐serine production. EXPERIMENTAL APPROACH: Following carrageenan injection, mechanical allodynia was tested at various time points to examine the effect of individual drugs. Immunohistochemistry and Western blot analyses were performed to clarify the expression levels of spinal D‐serine, serine racemase, σ1 receptors and connexin 43. KEY RESULTS: The expression of ipsilateral D‐serine was up‐regulated during the early phase of inflammation, while contralateral D‐serine increased during the later phase of inflammation. The pharmacological inhibition of D‐serine during the early phase blocked the development of both ipsilateral and contralateral mechanical allodynia. However, the inhibition of D‐serine during the later phase of inflammation blocked contralateral, but not ipsilateral mechanical allodynia. Furthermore, the inhibition of σ1 receptors during the earlier phase of inflammation inhibited the increase in ipsilateral D‐serine. Conversely, the blockade of astrocyte gap junctions suppressed the up‐regulation of contralateral D‐serine during the later phase of inflammation. CONCLUSION AND IMPLICATIONS: Spinal astrocyte D‐serine plays an important role in the development of mirror‐image pain. Furthermore, σ1 receptors and astrocyte gap junction signalling mediate ipsilateral and contralateral D‐serine production respectively.